Article RETRACTED due to manipulation by the authorsp Differences in Archery Skill Results for Vocational School Students and Beginners Based on Shooting Distance - Cholimah Mulyanti; Yudik Prasetyo; Sumarjo Sumarjo; Hendra Setyawan; Ari Wibowo Kurniawan; Abdul Aziz Purnomo Shidiq; Özgür Eken; Ratko Pavlovic; Francesca Latino; Francesco Tafuri; Tiok Wijanarko; Muhammad Imam Rahmatullah; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to examine differences in archery skill scores for Vocational High School (SMK) students among beginners based on the shooting target distance factors of 5 meters, 10 meters, and accumulated distances of 5 and 10 meters. The sample for this research was 16 male and female students from classes XA, XB and XIA, taken using the cluster random sampling method. Data analysis used descriptive statistics and inferential factorial one-way Anova. One-way anova test results Sig. 0.030 < 0.05 means there is a significant difference in the average of the three students' archery skill score results at a distance of 5 m, a distance of 10 m, and an accumulated distance of 5 and 10 m. First Post Hoc follow-up test Sig value. 0.088 > 0.05, meaning that there is no significant difference between the results of students' archery skills at a shooting distance of 5 m and a shooting distance of 10 m. Post Hoc follow-up test for both Sig values. 0.917 > 0.05, meaning that there is no significant difference in the results of students' archery skills at a shooting distance of 5 m with accumulated shooting distances of 5 and 10 m. Post Hoc follow-up test for the three Sig values. 0.036 > 0.05, meaning that the results of students' archery skills at a shooting distance of 10 m with an accumulated shooting distance of 5 and 10 m have a significant difference. Thus, it can be concluded that there is a significant difference in the average of the three students' archery skill score results at a distance of 5 m, a distance of 10 m, and an accumulated distance of 5 and 10. The findings of this study suggest the design of an archery training program for beginners, including consideration of starting from a shorter distance and gradually increasing the shooting distance, as well as carrying out various training techniques with a combination of exercises at various appropriate distances and giving priority to the consistency of technical movements and body posture. while archery.